PARTISIPASI MASYARAKAT DALAM PROGRAM KONSERVASI MALEO (Macrocephalon maleo) DI DESA MATAINDO, KECAMATAN PINOLOSIAN TENGAH, KABUPATEN BOLAANG MONGONDOW SELATAN - Balobahani ., Balantukang; Joachim N.K. Dumais; Ribka M. Kumaat (AGRI-SOSIOEKONOMI, 2015)
The objective of this study is to know the shape and the role of level of community participation in conservation programs Maleo (Macrocephalon maleo) in Mataindo Vilage, the research was conducted in Mataindo Vilage, sub distric Pinolosian Tengah, districs Bolaang Mongondow Selatan. The data collections have done by interviews. To specify of the sample to be interview are using the method simple random sampling. That the sampling of community randomly. With the total sample of 20 of respondents is obtained. Respondents interviewed were respondents lived 20 - 40 years old, age 41 - 50 years old, and 51 years and older. Mataindo village directly adjacent to the village Torosik in the east, west to the village Lungkap, south Maluku Sea, and north to the village of North Mataindo. The total area of the village of Mataindo is Â± 3500 mÂ² of the area of the District Middle Pinolosian. At this stage of planning with a form of activity following the meeting, to provide suggestion/ ideas, and get involved in decision making and implementation phase in the form of activity of making hathceries (nesting place) and plantation product (post-harvest) as well as monitoring activities. Based on the role of the level of community participation in the in conservation program maleo in Mataindo for village the planning, implementation and monitoring of are categorized be in between the active enough and activie.